A novel leptospiral protein increases ICAM-1 and E-selectin expression in human umbilical vein endothelial cells - Vieira, Monica L. (2007)
It has been reported previously that activation of vascular endothelium by outer membrane proteins of the spirochetes Borrelia sp. and Treponema sp. resulted in enhanced expression of endothelial cell adhesion molecules. To investigate the role of leptospiral proteins in this process, a predicted lipoprotein encoded by the gene LIC10365 was selected, which belongs to a paralogous family that presents a domain of unknown function, DUF1565. The LIC10365 gene was cloned and the protein expressed in Escherichia coli C43 (DE3) strain using the vector pAE. The recombinant protein tagged with N-terminal hexahistidine was purified by metal-charged chromatography and was used to assess its ability to activate cultured human umbilical vein endothelial cells. The rLIC10365 activated endothelium in such a manner that E-selectin and intercellular adhesion molecule 1 (ICAM-1) became upregulated in a dose-dependent fashion. The LIC10365-encoded protein was identified in vivo in the renal tubules of animal during experimental infection with Leptospira interrogans. Collectively, these results implicate the LIC10365-coding protein of L. interrogans as a potential effector molecule in the promotion of a host inflammatory response. This is the first report of a leptospiral protein capable of up-regulating the expression of endothelial cell adhesion molecules ICAM-1 and E-selectin.